A concise review of synthetic xanthone derivatives for Alzheimer's disease - Lokman Ali Ahmed; Hiyashree Sharmah (Brain Disorders)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder and the leading cause of dementia worldwide, characterized by cognitive decline, memory loss and behavioural changes. Despite extensive research, current therapies provide only symptomatic relief, underscoring the urgent need for novel, multi-targeted treatment strategies. Among emerging therapeutic candidates, synthetic xanthone derivatives have gained attention due to their structural versatility and ability to modulate several key pathological targets associated with AD, including acetylcholinesterase (AChE), butyrylcholinesterase (BuChE), amyloid-β aggregation, oxidative stress and neuroinflammation. This review offers a comprehensive analysis of synthetic xanthone derivatives studied between 2010 and 2023, emphasizing their structure-activity relationships and molecular mechanisms of action. Unlike prior literature, which often centres on natural xanthones, this work uniquely focuses on synthetic analogues, highlighting their advantages in fine-tuning biological activity and improving drug-like properties. Substitution patterns, particularly at positions 2, 3, and 6 of the xanthone scaffold, are shown to critically influence enzyme inhibition and selectivity. While promising in vitro and in silico results have been reported, further in vivo studies and clinical evaluations are essential to realize their therapeutic potential. This review aims to serve as a targeted resource for medicinal chemists and neuroscientists in the ongoing pursuit of next-generation anti-Alzheimer’s agents.